2016
DOI: 10.7150/thno.14937
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Laser-Controlled Drug Release from DOX/IR-780-Loaded Temperature-Sensitive-Liposomes for Chemo-Photothermal Synergistic Tumor Therapy

Abstract: NIR laser-induced photothermal therapy (PTT) through near-infrared agents has demonstrated the great potential in solid tumor ablation. However, the nonuniform heat distribution over tumors from PTT makes it insufficient to kill all tumor cells, resulting in tumor recurrence and inferior outcomes. To improve the tumor treatment efficacy, it is highly desirable to develop the combinational treatment of PTT with other modalities, especially with chemotherapeutic agents. Here we report a smart DOX/IR-780-loaded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 51 publications
3
106
0
Order By: Relevance
“…The appearance of voids in tumor section was associated with the loss of dead tumor cells. 34 Saline and DEX-SS-IND displayed intact nuclei morphology, suggesting negligible apoptosis or necrosis. Compared with free DOX and DEX-IND/ DOX micelles, more voids in tumor section was observed in tumor-bearing mice treated with DEX-SS-IND/DOX micelles, suggesting DEX-SS-IND/DOX micelles could effectively suppress MDR and exert antitumor efficacy.…”
Section: Histological Analysismentioning
confidence: 99%
“…The appearance of voids in tumor section was associated with the loss of dead tumor cells. 34 Saline and DEX-SS-IND displayed intact nuclei morphology, suggesting negligible apoptosis or necrosis. Compared with free DOX and DEX-IND/ DOX micelles, more voids in tumor section was observed in tumor-bearing mice treated with DEX-SS-IND/DOX micelles, suggesting DEX-SS-IND/DOX micelles could effectively suppress MDR and exert antitumor efficacy.…”
Section: Histological Analysismentioning
confidence: 99%
“…It has been reported that IR780 could effectively produce heat and generate singlet oxygen after irradiation with 808 nm laser, suggesting that IR780 can be an ideal agent for PTT and PDT. 17,18 In our proposed drug delivery system, HSA is a biocompatible and biodegradable carrier platform to deliver DTX, an effective antitumor drug, and IR780, a PTT/PDT agent. Furthermore, IR780 could also serve as a fluorescent imaging probe.…”
mentioning
confidence: 99%
“…To exemplify, Caixia Yue et al, (2013) reported that the IR-780 dye loaded tumor targeting theranostic nanoparticles for NIR imaging and PTT in which loading therapeutics agents would be difficult as the carrier is made of hydrophilic heparin. [8] A similar work was done by Fei Yan et al, (2016) where they used liposomes for co-loading IR-780 and DOX for treating breast cancers. However, the major limitation of their study is the intratumoral injection, which could reduce the efficacy when translating it in human use.…”
Section: Resultsmentioning
confidence: 94%
“…[8] A similar work was done by Fei Yan et al, (2016) where they used liposomes for co-loading IR-780 and DOX for treating breast cancers. [15] Since the chemo-agent DOX must be precisely released inside the tumor cells only on NIR irradiation, NEMSn would be a better option. [15] Since the chemo-agent DOX must be precisely released inside the tumor cells only on NIR irradiation, NEMSn would be a better option.…”
Section: Resultsmentioning
confidence: 94%